Dancing the World Smaller Staging Globalism in Mid-Century America - Kowal, Rebekah J. (Oxford Studies in Dance Theory, 2020)
This book examines international dance performances in New York City in the 1940s as sites in which dance artists and audiences contested what it meant to practice globalism in mid-twentieth-century America. Debates over globalism in dance proxied larger cultural struggles over how to reconcile the nation's new role as a global superpower. In dance as in cultural politics, Americans labored over how to realize diversity while honoring difference and manage dueling impulses toward globalism, on the one hand, and isolationism, on the other.